HLA-DQA1 and polymarker locus allele frequencies for Elazig/Turkey - Dulger, H. Ergin; Tokdemir, Mehmet (My University, 2000)
[Abstract Not Available]
Keywords: D7S8; DNA typing; Forensic science; GC; GYPA; HBGG; HLA- DQA1; LDLR; Population genetics; Turkey